Manajemen Dakwah Jema’ah Tablig dalam Meningkatkan Kesadaran Beribadah Masyarakat Kecamatan Medan Area - Baginda Pitra Setia Siregar; Abdullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
As time progresses, da'wah work continues to be carried out by each group of the Muslim movement which has its own way of carrying out its da'wah. One of them is the Tablighi Jema'ah. To awaken the spiritual spirit in the self and life of every Muslim, the Tablighi Jema'ah has its own management. This research will describe (1) how the management of the Tablighi Jema'ah increases awareness of worship in the Medan Area sub-district community. (2) Tablighi Jema'ah profile. (3) What are the obstacles faced in the da'wah management process by the Tablighi Jema'ah? The method used in this research is a qualitative method with data collection techniques in the form of interviews (randomly) and observation in the context of searching and extracting information and collecting data. The results of this research show that the Tablighi Jema'ah implements da'wah management in its da'wah process, namely using da'wah management functions (planning, organizing, mobilizing or implementing da'wah and evaluation). The material presented by the Tablighi Jema'ah was related to the mahdah worship and the rewards for good deeds performed. Apart from that, the Tablighi Jema'ah also invites congregational prayers at the mosque and brings the mosque to life. The Tablighi congregation conveys its preaching through studies and coming directly to people's homes. However, there are still several obstacles in the process of da'wah management, such as material readiness when preaching and responses in the community, but this is not a significant problem for them, because through good management all obstacles can be overcome well.